A novel sub-camera array model for calibrating multi-mirror catadioptric systems. (16th July 2015) - Xiang, Zhiyu; Zhou, Yanbing; Gong, Xiaojin
Abstract: The omni-directional catadioptric camera composed of multiple mirrors is a powerful tool that can acquire multiple wide field-of-view images and reconstruct the scene in a single shot. However, the non-central nature of the system poses significant challenges to the task of calibration. A novel off-center spherical projection (OCSP)-based sub-camera array model is proposed in this paper to address this problem. By inducing a movable spherical projection center in the traditional unified model, the OCSP sub-camera can efficiently deal with large misalignments that exist in multi-mirror systems. An efficient calibration method and the initialization algorithm are also presented. With the new model, calibration can be completed conveniently without the aid of a priori information on the mirrors and camera. The model is also compatible with traditional multi-view geometry, making 3D reconstruction straightforward for non-central systems. Experiments based on synthetic and real data on various types of mirrors show promising calibration results and thus verify the effectiveness of the method.